4(x-3)+1=6x-2(4+x)

Simple and best practice solution for 4(x-3)+1=6x-2(4+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-3)+1=6x-2(4+x) equation:


Simplifying
4(x + -3) + 1 = 6x + -2(4 + x)

Reorder the terms:
4(-3 + x) + 1 = 6x + -2(4 + x)
(-3 * 4 + x * 4) + 1 = 6x + -2(4 + x)
(-12 + 4x) + 1 = 6x + -2(4 + x)

Reorder the terms:
-12 + 1 + 4x = 6x + -2(4 + x)

Combine like terms: -12 + 1 = -11
-11 + 4x = 6x + -2(4 + x)
-11 + 4x = 6x + (4 * -2 + x * -2)
-11 + 4x = 6x + (-8 + -2x)

Reorder the terms:
-11 + 4x = -8 + 6x + -2x

Combine like terms: 6x + -2x = 4x
-11 + 4x = -8 + 4x

Add '-4x' to each side of the equation.
-11 + 4x + -4x = -8 + 4x + -4x

Combine like terms: 4x + -4x = 0
-11 + 0 = -8 + 4x + -4x
-11 = -8 + 4x + -4x

Combine like terms: 4x + -4x = 0
-11 = -8 + 0
-11 = -8

Solving
-11 = -8

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 1.67u-1.67=1.25-.67 | | 1.5x=x+15 | | 0.12(y-7)+0.18y=0.10y-0.6 | | .9y-3.6=-.3y+3 | | 7x-7=8+6x | | 3(4y+4)=10 | | 28x+35=8x-27 | | 4m=(m+4)(2-m) | | 14x-2=-3x-18 | | 7.25x+5.4y=730 | | 5.7x-3.1(x+5)=5.04 | | -2x/3-2-3 | | -[3z-(5z+8)]=8+(1z+7) | | 15x-25=4x+2 | | -15w+15=-15w+15 | | 9x+5=-8+3x+25 | | 6u+9=9u-18 | | 5x+2y-9z=13 | | 3x+10+6x-1=180 | | -8+3x=x-4 | | -8+x=x-4 | | a^2x+(a-1)=(a+1) | | 11-3x=-31 | | -15+n*2=15 | | -6z-18=9z+12 | | -15+n*2=13 | | 2(3x-2)=2(17x+14) | | 3x+15=8+x | | 5x+.6=1.8 | | 3w-2(.5w+1)=-4(2+w) | | -4x+1.1=-34.9 | | 28=t(r-4) |

Equations solver categories